Analysis of Thematic Learning Evaluation on Theme 8 "Safety at Home and Travel" in Grade 2 SDN 158 Palembang - Mardiah Astuti; Eby Sania Awalia; Meta Melinda; Rheina Nurhaliza Fatnasari; Fitriah Isnaini (Sustainable, 2023)
Thematic learning is an educational approach that integrates multiple subjects under a unified theme to enhance student engagement and comprehension. This study focuses on evaluating the implementation and effectiveness of thematic learning at SDN 158 Palembang, specifically in grade 2. Utilizing a qualitative descriptive method, data were collected through observation, interviews, and documentation. Findings reveal that teachers utilize diverse strategies, including active group learning and IT-based media, to enhance students' motivation and focus. However, challenges persist, particularly in managing group activities and addressing varying levels of student literacy. Teachers also face difficulties in teaching specific subjects like citizenship due to limited thematic book content, prompting the use of supplementary materials. Evaluation of thematic learning is conducted through regular assessments, including daily tests, midterms, and final exams, focusing on knowledge, skills, and attitudes. While thematic learning shows potential in fostering critical thinking and active participation, it also requires continuous teacher training and better resource allocation to address implementation challenges. The study concludes that thematic learning is effective in promoting holistic student development but necessitates improvements in evaluation methods and instructional resources for optimal results.